1Black Critical and Cultural Theory. - Anucha, Kelechi (Year's Work in Critical & Cultural Theory, 2020)
This chapter reviews black critical and cultural theory under the following headings: 1. Introduction; 2. Cultural Studies (Kara Keeling, Queer Times, Black Futures , Jennifer C. Nash, Black Feminism Reimagined: After Intersectionality , and Tiffany Lethabo King, The Black Shoals: Offshore Formations of Black and Native Studies); 3. History and Sociology (Saidiya Hartman, Wayward Lives, Beautiful Experiments , and Ruha Benjamin, Race After Technology: Abolitionist Tools for the New Jim Code); 4. Interdisciplinary Literary Studies (Therí Alyce Pickens, Black Madness :: Mad Blackness).